The validity and reliability of Persian version of smartphone addiction questionnaire in Iran - Zahra Shaahmadi; Touraj Ahmadi Jouybari; Bahare Lotfi; Abbas Aghaei; Reza Ghanei Gheshlagh (BMC, 2021)
Abstract Background Smartphone addiction is one of the most important forms of technology addiction that has attracted the attention of all countries around the world. Many studies have been conducted in Iran on cellphone addiction among different groups. There is a necessity to have a native scale for measuring smartphone addiction in particular. Therefore, this study aimed to localize the smartphone addiction questionnaire in Iran (in the Persian language). Methods To assess the validity and reliability of the Persian version of the smartphone addiction scale (SAS), the questionnaire was first provided based on the standard back-translation method. Next, content validity ratio (CVR), content validity index (CVI), and face validity was evaluated for translated questionnaire. After making the necessary changes, the questionnaire was given to the community samples and was then reviewed using confirmatory factor analysis of questions grouping. Finally, the reliability of the questionnaire was investigated by the test-retest method. Results The CVR and CVI values of all questions were within the acceptable range. Only some of the questions in the original SAS version titled Twitter and Facebook were changed to Instagram and telegram according to experts. Internal consistency and concurrent validity of the questionnaire were confirmed by Cronbach's alpha of 0.951. The mean correlation coefficient between the responses of the subjects, who received the questionnaire twice, was 0.946 (0.938-0.954). The grouping of questions in the subscales was changed from the original SAS version because the fitting indexes, obtained from the confirmatory factor analysis test (for example CMIN/DF greater than 5 units and RMSEA of approximately 0.07), were not acceptable. Conclusion The results showed that the Iranian version of the cellphone addiction questionnaire can be used as a valid, with minimal modification, tool for determining the level of smartphone addiction among Persian speakers.